Increased Purchase Decision of Le Minerale through Perceived Quality and Brand Image - Achmad Ramadhani; Arry Widodo (Pusat Penerbitan dan Publikasi Ilmiah, Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2021)
This research determines the perceived quality effect on Le Minerale purchasing decisions through brand image in Bogor Regency. The method is quantitative with causal and descriptive types. The population is people of Bogor Regency who purchased Le Minerale and needed 100 respondents. The descriptive analysis and Structural Equation Model with SmartPLS are the research techniques. The results, perception of quality as a whole is included in good category (78.18%), brand image as a whole is included in good category, 86.80%, and overall purchasing decisions are included in good category, 78.96%. It means perceived quality has a positive effect on brand image, brand image has a positive effect on purchasing decisions and perceived quality affects purchasing decisions.